Determination of Causes of Psychic Indisposition is Described Unconsciously or Discretely in 7x4-Field form in Famous Works of Art - Heiska, Juhani (Selected Topics in Humanities and Social Sciences Vol. 4, 2021)
The 7x4-field is a tool for analysing and describing mental disorders, illnesses, anomalies, and malaise, as well as general human suffering. It was created utilising a combination of actual mental health work and extensive interviews, as well as factor analysis.It can also be used to deal with a variety of distress and mental health issues. It allows for a more comprehensive perspective of these processes than is possible with still pictures. This article investigates the observation that many renowned works of art explain the same aspects that are provided in 7x4-field's different squares, as well as how to apply the findings to education, culture, and other fields.